2022
DOI: 10.1097/ta.0000000000003537
|View full text |Cite|
|
Sign up to set email alerts
|

Beta blockade in TBI: Dose-dependent reductions in BBB leukocyte mobilization and permeability in vivo

Abstract: Beta blockade in severe traumatic brain injury has shown improvements in survival and recovery after injury. This paper demonstrates in a series of in vivo and ex vivo experiments a potential mechanism for this benefit using a live rodent TBI model.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
8
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 11 publications
(8 citation statements)
references
References 48 publications
0
8
0
Order By: Relevance
“…After TBI, the BBB is damaged, resulting in increased permeability and severe brain edema ( 31 33 ). Previous studies have demonstrated that the posttraumatic inflammation cascade promotes TBI-induced BBB disruption ( 10 ).…”
Section: Resultsmentioning
confidence: 99%
“…After TBI, the BBB is damaged, resulting in increased permeability and severe brain edema ( 31 33 ). Previous studies have demonstrated that the posttraumatic inflammation cascade promotes TBI-induced BBB disruption ( 10 ).…”
Section: Resultsmentioning
confidence: 99%
“…Beta blockers may also modulate the post-TBI catecholamine surge which can also contribute to secondary cerebral injury through worsening cerebral hypertension and edema ( 24 ). It is also possible that lipid-soluble beta blockers could cross the blood-brain barrier and exert their effects directly on cerebral tissue and vasculature, preventing ischemia by decreasing vasoconstriction, though this mechanism is largely theoretical ( 24 , 25 ). Finally, beta blockers’ cardioprotective effects may be a driving benefit, by reducing the risk of subsequent myocardial infarction by decreasing stroke volume, heart rate, blood pressure, and myocardial oxygen demand ( 24 , 26 ).…”
Section: Discussionmentioning
confidence: 99%
“…It has been shown that TBI patients experience sympathetic hyperactivity, causing a catecholamine surge [213][214][215][216][217][218]. This surge causes secondary insults, which manifest as posttraumatic hyperthermia [216,218], increased inflammation and leukocyte migration [219,220], impaired cerebral homeostasis and perfusion [217], and cardiovascular dysfunction [216], and has been associated with increased mortality [221]. In light of such evidence, the use of beta-blockers to alleviate secondary damage caused by TBI gained interest.…”
Section: Beta-blockersmentioning
confidence: 99%